Fire management in the American West : forest politics and the rise of megafires - Hudson, Mark, 1971 June 27- (University Press of Colorado, 2011)
Most journalists and academics attribute the rise of wildfires in the western United States to the USDA Forest Service's successful fire-elimination policies of the twentieth century. However, in Fire Management in the American West, Mark Hudson argues that although a century of suppression did indeed increase the hazard of wildfire, the responsibility does not lie with the USFS alone. The roots are found in the Forest Service's relationships with other, more powerful elements of society--the timber industry in particular. Drawing on correspondence both between and within the Forest Service a.